Avaliação técnica da gaseificação do bagaço de cana-de-açúcar em reator contínuo de leito fluidizado - Alves, Vittor Rodrigues Santos (Universidade Federal de São Carlos, 2020)
The sugar and alcohol sector introduces a big potential to expand the production lines of ethanol, sugar and clean electric energy with a profitable harnessing of its residues and sub products, like sugar cane bagasse. The gasification is a thermo chemical process that converts carbonaceous matter in a gas with attractive energetic properties which is composed of H2 and CO mainly. The objective of this work is to analyze the sugar cane bagasse gasification aiming at the production of a syngas rich in H2 and CO, searching process conditions that maximize its concentrations. Therefore, it was used a continuous fluidized bed reactor applying experimental planning to investigate the effect of the equivalent ratio (ER) and the steam/biomass relation (S/B) in the H2 content. The results show that these variables impact the production of H2. The maximum experimental H2 concentration obtained was equal to 16.97% v/v using ER=0.23 and S/B=0.92; whereas the maximum of the model was equal to 17.38% v/v. For CO, the maximum experimental concentration was 36.13 % v/v using ER = 0.31 and SB = 0.92. Mass balances in some regions show that the gasification with the smallest ER produces the highest H2 and CO concentrations, but with bigger tar formation that can be bad to syngas quality. Moreover, inside the analyzed region the presence of other compounds like Benzene (C6H6) and Toluene (C7H8) was observed.
Technical evaluation of gasification of sugarcane bagasse in continuous fluidized bed reactor
Keywords: Gaseificação; Cana-de-açúcar; Gás de síntese; Leito fluidizado; Gasification; Sugar-cane; Syngas; Fluidized bed; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA